Bottom-up initiatives toward climate change adaptation in cases in the Netherlands and the UK: a complexity leadership perspective. (October 2015) - Scholten, P; Keskitalo, ECH; Meijerink, S
Climate change will result in large challenges that require societies to adapt to and manage increased risks. Regional practices of climate adaptation often take shape within multilevel governance networks in which representatives of different levels of government, policy sectors, public and private parties may discuss and negotiate potential measures. This paper aims to explore the role of leadership in enhancing the adaptive capacity of multilevel governance networks and in supporting regional practices of climate adaptation. The paper reviews two initiatives toward climate adaptation, the WaalWeelde initiative in the Netherlands and the Manhood Peninsula Partnership in the UK, based on policy documentation and analysis of in total 17 semistructured interviews with public and private actors. The study illustrates both the large differences in organization of water management, spatial planning, and flood risk policies, as well as strong similarities in the way in which leadership may contribute to the development of initiatives.